Does polyploidy inhibit sex chromosome evolution in angiosperms? - He, Li; Hörandl, Elvira (Frontiers in Plant Science, 2022)
Dioecy is rare in flowering plants (5-6% of species), but is often controlled genetically by sex-linked regions (SLRs). It has so far been unclear whether, polyploidy affects sex chromosome evolution, as it does in animals, though polyploidy is quite common in angiosperms, including in dioecious species. Plants could be different, as, unlike many animal systems, degenerated sex chromosomes, are uncommon in plants. Here we consider sex determination in plants and plant-specific factors, and propose that constraints created at the origin of polyploids limit successful polyploidization of species with SLRs. We consider the most likely case of a polyploid of a dioecious diploid with an established SLR, and discuss the outcome in autopolyploids and allopolyploids. The most stable system possibly has an SLR on just one chromosome, with a strongly dominant genetic factor in the heterogametic sex (e.g., xxxY male in a tetraploid). If recombination occurs with its homologue, this will prevent Y chromosome degeneration. Polyploidy may also allow for reversibility of multiplied Z or X chromosomes into autosomes. Otherwise, low dosage of Y-linked SLRs compared to their multiple homologous x copies may cause loss of reliable sex-determination at higher ploidy levels. We discuss some questions that can be studied using genome sequencing, chromosome level-assemblies, gene expression studies and analysis of loci under selection.